Modal analysis of a submerged spherical point absorber with asymmetric mass distribution. (January 2019) - Meng, Fantai; Ding, Boyin; Cazzolato, Benjamin; Arjomandi, Maziar
Abstract: Of all the wave energy converter (WEC) categories, the single-tether point absorber (PA) is one of the most widely used in the ocean renewable energy industry. In most published research, only the heave motion of the buoy is considered in the motion equation for the analysis. This is because the heave motion of the buoy strongly couples to the power take-off device (PTO), whereas the surge and pitch motions barely couple to the PTO. As a result, only the power arising from heave motion of the buoy can be efficiently absorbed when a single-tether PTO is used, leading to deficiency of the design in absorbing the power arising from its surge and pitch motion. In this paper, the deficiencies of single-tether PAs are addressed by simply shifting the center of gravity of the buoy away from its geometric centre. A spherical buoy with asymmetric mass is used in this paper for its simplicity. The asymmetric mass distribution of the buoy causes motion coupling across surge, heave and pitch motions, which enables strong coupling between the buoy's surge motion and the PTO movement. The operation principle and power generation of the spherical point absorber with asymmetric mass distribution (SPAMD) are investigated via a modal analysis conducted on a validated frequency-domain model. The results show that the SPAMD can be up to 3 times more efficient than the generic PAs when subjected to regular waves in the frequency range from 0.34 rad/sec to 1.4 rad/sec. Highlights: Significant efficiency improvement of a single-tethered point absorber by utilizing motion-coupling. 3DOF frequency domain model with linearised viscous drag forces. Using model analysis to understand the dynamic of system. Identification of key factors for efficiency improvement. Identification of operation regimes of system throughout wave frequencies.